(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the problem of increasing the fertility of irrigated lands through economic methods. It considers factors such as subsidies, tax benefits, and financial allocations used in foreign countries to maintain and increase soil fertility. Additionally, it outlines directions for enhancing soil fertility using modern methods, particularly digital technologies, investment incentives, subsidy systems, and agrotechnical measures.